HYBRID POWER GENERATION WITH MINI WIND MILL AND SOLAR PANEL “A FUTURE ENERGY SOLUTION FOR DOMESTIC POWER REQUIREMENT” - Garala, Brijesh M. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Energy is the primary and most universal measure of all kinds of work by human beings and nature. Everything what happens in the world is the expression of flow of energy in one of its forms. Energy is an important input in all sectors of any country’s economy. The standard of living of a given country can be directly related to per capita energy consumption. Energy crises are due to the two reasons; firstly the population of world has increased rapidly and secondly the standard of living of human beings has increased. To fulfill the increasing demand of energy, conventional energy source is not sufficient. That’s why now a days it is more important to fulfill the energy demand with the help of non conventional energy sources. In this paper an attempt is made to study the design and development parameters for mini wind mill used in domestic applications like generate small capacity power for buildings, households, commercials, small industry etc. effectively.